If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(b + 5) = -2(6b + 6) Reorder the terms: -6(5 + b) = -2(6b + 6) (5 * -6 + b * -6) = -2(6b + 6) (-30 + -6b) = -2(6b + 6) Reorder the terms: -30 + -6b = -2(6 + 6b) -30 + -6b = (6 * -2 + 6b * -2) -30 + -6b = (-12 + -12b) Solving -30 + -6b = -12 + -12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12b' to each side of the equation. -30 + -6b + 12b = -12 + -12b + 12b Combine like terms: -6b + 12b = 6b -30 + 6b = -12 + -12b + 12b Combine like terms: -12b + 12b = 0 -30 + 6b = -12 + 0 -30 + 6b = -12 Add '30' to each side of the equation. -30 + 30 + 6b = -12 + 30 Combine like terms: -30 + 30 = 0 0 + 6b = -12 + 30 6b = -12 + 30 Combine like terms: -12 + 30 = 18 6b = 18 Divide each side by '6'. b = 3 Simplifying b = 3
| 1a+15b-1a+5b= | | 11*3*x=11x | | n+228=-8n+3 | | 75-9h=-20+10th | | 8x+3(x-2)=4 | | 70+70*0+1= | | e-109=-e-9 | | -2n-6(1-10n)=-4n-9(-6-8n) | | Ab+3c=2xform | | 0.20+(0.30)(25)=(0.27)(x+25) | | 4(2x-6)=5(x+4) | | 8x=158 | | 2(x+0.5)=24 | | -45x+270=y | | 5y-2(y+2)= | | 6/10=p/4 | | 15y-45x=-30 | | -45+270=y | | 2/4=5v/5 | | -w-7=w+41 | | 12n^2-18n=0 | | 3k-5k=7k+7 | | 8/3=2/r | | m-30=-m-4 | | t/4-8=9 | | 5x^2-32x+10=0 | | n/7=5/4 | | -k=x^2-6x | | -12=6+4t | | 7(2x-2)-6(3-3x)=0 | | -x+3=x+37 | | y=-7(17/18) |